Pelatihan Bela Negara untuk Meningkatkan Kompetensi dan Nasionalisme Mahasiswa PPG Universitas Cenderawasih - Efendi, Rian; Mutaqin, Alim; Simorangkir, Agustina; M. Raidil; Wijaya, Silvia Anggri; Pamangin, Wilda Wijayani (Journal of Social and Community Service, 2024)
National defense training for prospective teachers is a strategic effort to develop resilient, disciplined educators with a strong sense of national identity. This article presents an evaluation of a community service program in the form of national defense training assistance for 21 students of the first cohort of the Teacher Professional Education (PPG) program at Cenderawasih University. The three-day program was conducted at the National Defense Education Depot, RINDAM XVII Cenderawasih, combining interactive lectures, simulations, and field practices such as drill regulations (PBB), ceremonial procedures, group dynamics, and field psychology. The experiential learning approach and collaboration with the military were key to the program's implementation. Evaluation through pretest-posttest and participatory observation revealed significant improvements: all participants (100%) achieved the Minimum Mastery Criteria (KKM) in the posttest, compared to only 14.29%-38.10% in the pretest. The greatest improvement was in drill regulations (85.71%), followed by military honors (80.95%), and national insight (71.43%). Qualitatively, participants showed enhanced discipline, teamwork, confidence, and understanding of national values. Activities such as campfires and field psychology simulations further strengthened solidarity and leadership skills. This program demonstrates the effectiveness of integrating experience-based training and educational-military partnerships in preparing prospective teachers as agents of character development for the younger generation. The results recommend incorporating similar training models into the PPG curriculum to reinforce the academic, social, and nationalistic competencies of future educators.